STUDY PENDAHULUAN SESAR OPAK DENGAN METODE GRAVITY (STUDY KASUS DAERAH SEKITAR KECAMATAN PLERET BANTUL) - Nurwidyanto, M Irham; Brotopuspito, Kirbani Sri; Waluyo, Waluyo; Sismanto, Sismanto (BERKALA FISIKA, 2011)
The reconnaissance research to predict the position and the type of Opak Fault in surrounding subdistrict Pleret area was carryout by gravity method. It done by measured the intensity of gravity field. The measurement was done in five lines cross the Opak Fault which indicated in the geological map. The intensity of gravity field in the surround of subdistrict Pleret area are measured by la-coste Romberg Gravitymeter, the latitude are measured by GPS Trimble, and the position are measured by GPS Garmin III Plus. The measurement was done in five lines which separated abaut 2,5 km and about 20 km in length. The distance of observations are about 0,5 km to 1 km. The data which be collected are reduction by drift and tidal correction, free air correction, bouger correction and terrain correction. The corrected data are made bouger anomaly contour. The result of this research by kwalitative interpretation are estimated that the location of Opak Fault in the eastern part of the position of Opak Fault which indicated in the geological map. The type of opak fault are normal fault, because can be detected by gravity method. Key words : Opak Fault, Pleret, gravity method.